Metabolic predictors of impaired glucose tolerance and type 2 diabetes in a predisposed population – A prospective cohort study - Henninger, Josefin (BMC Endocr Disord, 2015)
BACKGROUND: We characterized in detail (oral and intravenous glucose tolerance tests (OGTT and IVGTT), euglycemic hyperinsulinemic clamp, adipose tissue biopsy), healthy first-degree relatives (FDR) of individuals with type 2 diabetes (T2D), to examine predictive factors for future development of impaired glucose tolerance (IGT) or T2D. METHODS: Non-diabetic FDR (n = 138, mean age 40.5 ± 6.5 years, 57 % women) underwent an extended OGTT every 3 years to assess any deterioration in glucose tolerance status. Differences between groups were assessed by logistic fit for continuous variables and by contingency analysis for categorical variables. Multiple logistic regression analysis was applied to adjust for confounding variables. RESULTS: At follow-up (mean 5.6 ± 2.4 years) 19 subjects had IGT and 4 had T2D. At baseline these 23 subjects had more family members with T2D, higher fasting plasma glucose, higher OGTT plasma glucose at 120 min, higher HbA1c, lower M-value and higher total cholesterol compared to subjects with normal glucose tolerance (NGT). There were significantly larger changes in weight, BMI, fasting plasma glucose, OGTT plasma glucose at 120 min and HbA1c in individuals developing IGT or T2D during the follow-up period than the subjects remaining NGT. Crude predictors of deteriorating glucose tolerance were age, family history of diabetes and of hypertension, OGTT plasma glucose levels at 60 min, 90 min, and 120 min, as well as serum bilirubin, ALP and creatinine (p-values <0.05). A multiple nominal logistic regression model revealed that male sex, low M-value and high physical exercise (p-values <0.05) predicted development of IGT/T2DM. CONCLUSION: In sum, genetically predisposed individuals for T2D with deteriorating glucose tolerance exhibit insulin resistance as well as beta-cell and signs of adipose tissue dysfunction, emphasizing the multifactorial pathophysiology in the development of IGT and T2D.